2019
DOI: 10.1016/j.cyto.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated peripheral blood mononuclear cells from chlamydia-infected women release predominantly Th1-polarizing cytokines

Abstract: Chlamydia trachomatis infection (chlamydia) is the most prevalent sexually transmitted bacterial infection and causes significant reproductive morbidity in women. Little is known about how immunity to chlamydia develops in women, though animal models of chlamydia indicate that T-helper type 1 (Th1) responses are important for chlamydia clearance and protective immunity, whereas T-helper type 2 (Th2) responses are associated with persisting infection. In chlamydia-infected women, whether the predominant immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The results from this work helped enable a better understanding of mitochondrial damage and cell heterogeneity (Kummer and Wilichowski 2018). LCM has played a role in single-inclusion level by isolating Chlamydia trachomatis-infected cells to study the generation of microbiological clones of C. trachomatis, and molecular assay tests to the isolated chlamydia cells to study cell features (Jordana et al 2016).…”
Section: Laser and Vacuum Microdissectionmentioning
confidence: 99%
“…The results from this work helped enable a better understanding of mitochondrial damage and cell heterogeneity (Kummer and Wilichowski 2018). LCM has played a role in single-inclusion level by isolating Chlamydia trachomatis-infected cells to study the generation of microbiological clones of C. trachomatis, and molecular assay tests to the isolated chlamydia cells to study cell features (Jordana et al 2016).…”
Section: Laser and Vacuum Microdissectionmentioning
confidence: 99%
“…In a recent proof-of-principle vaccine study using TriAdj-adjuvanted UV-inactivated Cs as the vaccine, we demonstrated that this proof-of-principle vaccine induced a robust CD4 IFN-γ (=T-helper 1, Th1) response which is considered the mechanism of protection for various intracellular bacteria, including Ct, as reviewed in [5]. This Th1 response has been shown to be critical in the anti-Ct response [5,[30][31][32][33]. In addition, upon challenge with Cs, our TriAdj-adjuvanted UV-Cs vaccine candidate reduced the genital Cs load compared to unvaccinated pigs, demonstrating vaccine efficacy.…”
Section: Introductionmentioning
confidence: 95%
“…CD4 T cells in human Chlamydia infection secrete significant levels of IFN-γ [27,28]. Similarly, CD4 T cells recovered from the FRT of Chlamydia-infected mice secrete IFN-γ [19], while mice genetically deficient in IFN-γ or IFN-γR suffer from an overwhelming systemic infection [29,30].…”
Section: Introductionmentioning
confidence: 99%